The impact of integrating infographics into English language instruction on mother tongue use and reading/writing performance: A systematic literature survey - Mushir, Tavga; Bostanci, Hanife Bensen; Koç, Sabri (Research Journal in Advanced Humanities, 2023)
In contemporary instructional programs for teaching English as Foreign Language (EFL) all over the world, the application of infographics has become essential for improving students' language skills, in particular reading and writing skills. In many countries worldwide, students have been encouraged through the use of infographics in their English language courses to achieve a high level of proficiency and become competent language learners. This research study aims to examine the influence of integrating infographics into the EFL reading and writing courses. To achieve this aim, the research study focuses on a systematic literature review by investigating 21 papers in the field of teaching EFL. Since students are allowed to use only English for communication in class, it appears to many students as a difficult language to learn. The findings of the literature survey indicate that one of the main obstacles to learning a foreign language seems to be the learners' native language, which must also be considered in organizing foreign language teaching curricula. Another obstacle is that learners have limited opportunities to use their English in reading and writing skills outside the classroom.